A novel phosphorus-containing lignin-based flame retardant and its application in polyurethane. (October 2020) - Wang, Yuliang; Zhang, Yumei; Liu, Biying; Zhao, Qi; Qi, Yunxia; Wang, Yanmiao; Sun, Zhaoyan; Liu, Baijun; Zhang, Niaona; Hu, Wei; Xie, Haiming
Abstract: A novel lignin-based flame retardant (LMD) is synthesized in this work via the in-situ reactions of lignin, diphenylmethane diisocyanate (MDI), and 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO). Flame-retardant polyurethane (FLPU) is prepared by the co-curing of LMD and prepolymer synthesized by lignin, MDI, and polyether polyol 204. Polyethylene glycol (PEG) 2000 is also added to adjust the flexibility of the lignin-based polyurethane (LPU). The limiting oxygen index (LOI) value of the FLPU gradually increases with the LMD content and can reach 29.9% for F30-L20 -L15-80 PU (L20MD content is 30% in L15-80 PU), exhibiting excellent flame-retardant properties. The hardness of the FLPU for the optimized formulation is 2H, the adhesion is 0, and the flexibility is 2 mm. And the impact resistance is greater than 100 cm/1000 g. These outstanding properties illustrate the LMD is excellent flame retardants and reinforcing materials for LPU. The interface can be strengthened by the co-curing between the LMD and the LPU prepolymer. Highlights: Lignin-based flame retardant (LMD) was synthesized. FLPU was prepared by co-curing of LMD and prepolymer. PEG was used to adjust the flexibility. FLPU has high LOI value and outstanding coating properties.